Rx - Lynn, Tracy (New York : Simon Pulse, 2015)
Thyme Gilchrest is an honors student. Thyme Gilchrest is popular. Thyme Gilchrest is on student council. Thyme Gilchrest is a drug dealer. Like piecing together a logic puzzle, Thyme has organized a complex trading system that enables her to obtain the meds her friends need. They all come to her to diagnose their problems and provide the "cure"--be it Prozac, Ritalin, Vicodin. She's a therapist, doctor, and pharmacist all in one. She helps people. And that makes her feel a little more in control, a little more capable of dealing with her own frantic high school life. Because Thyme Gilchrest is nothing if not good at dealing.
Keywords: Drug dealers -- Fiction; Thrillers (Fiction)